Marital Monogamy as Ideal and Practice: The Detraditionalization Thesis in Contemporary Marriages. Issue 2 (30th December 2015) - Green, Adam Isaiah; Valleriani, Jenna; Adam, Barry
Abstract : Within the sociological literature on intimate life, a detraditionalization thesis outlines a marked shift in the construction of marriage in post‐World War II Western societies, suggesting a growing focus on emotional and sexual satisfaction within the marital dyad (Cherlin, 2004; Giddens, 1992). In this article the authors investigated one aspect of marital relations in light of the detraditionalization thesis: marital monogamy. Drawing from 90 in‐depth interviews with both heterosexual and same‐sex married participants in Canada, they found that the detraditionalization thesis appears to capture best the extension of multicultural norms to abstract ideals about marital monogamy, rather than an actual shift in marital sexual practices, particularly among heterosexual respondents. These data call out for greater attention to both the social mediation of Giddens's detraditionalization thesis and a more nuanced concept of marital fidelity than a simple binary axis of "monogamous/nonmonogamous" permits.